2018
DOI: 10.1158/1541-7786.mcr-17-0334
|View full text |Cite
|
Sign up to set email alerts
|

Epigenetically Regulated Chromosome 14q32 miRNA Cluster Induces Metastasis and Predicts Poor Prognosis in Lung Adenocarcinoma Patients

Abstract: Most lung cancer deaths are related to metastases, which indicates the necessity of detecting and inhibiting tumor cell dissemination. Here, we aimed to identify miRNAs involved in metastasis of lung adenocarcinoma as prognostic biomarkers and therapeutic targets. To that end, lymph node metastasis-associated miRNAs were identified in The Cancer Genome Atlas lung adenocarcinoma patient cohort (sequencing data; = 449) and subsequently validated by qRT-PCR in an independent clinical cohort ( = 108). Overexpressi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
28
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(31 citation statements)
references
References 47 publications
2
28
1
Order By: Relevance
“…Among them, we found the upregulation of onco‐miRNA hsa‐miR‐21‐5p and six miRNAs encoded by the 14q32 region, which contains two miRNA clusters located within an imprinted locus . Remarkably, the upregulation of these miRNA clusters has been previously associated with poor outcome disease in other solid tumors …”
Section: Resultsmentioning
confidence: 81%
See 1 more Smart Citation
“…Among them, we found the upregulation of onco‐miRNA hsa‐miR‐21‐5p and six miRNAs encoded by the 14q32 region, which contains two miRNA clusters located within an imprinted locus . Remarkably, the upregulation of these miRNA clusters has been previously associated with poor outcome disease in other solid tumors …”
Section: Resultsmentioning
confidence: 81%
“…15 Remarkably, the upregulation of these miRNA clusters has been previously associated with poor outcome disease in other solid tumors. 16,17 Twenty nine miRNAs were associated with the prognosis of RAS-mutant tumors (Supporting Information Table S3 and Fig. S2a).…”
Section: Differential Expression Analysis Of the Mirnome Reveals Progmentioning
confidence: 99%
“…In agreement with our findings, similar studies have already been carried out for the identification of prognostic miRNA signatures from the TCGA in other types of cancers, including bladder cancer, glioblastoma, colon cancer, etc. (Gonzalez-Vallinas et al, 2018;Hermansen et al, 2017;Liu et al, 2017a;Wong et al, 2016;Xu et al, 2016;Zhou et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, several studies have shown that miRNA clusters comprise of two or more miRNA genes that display high level of identity in sequences. Moreover, they are situated contiguously with each other in the genome (Gonzalez-Vallinas et al 2018). Through experimental and computational identification, the miRBase database is one of the primary repository resources for collecting miRNA genes (Griffiths-Jones et al 2007;Kozomara and Griffiths-Jones 2013).…”
Section: Discussionmentioning
confidence: 99%